New findings of Coprinellus species (Psathyrellaceae, Agaricales) in China - Huang, Mei; Bau, Tolgor (Phytotaxa, 2018)
Two taxa of Coprinellus from China are described on the basis of morphological features and phylogeny. Coprinellus pseudodisseminatus is described as a new species in Coprinellus section Setulosi due to its milky-white to pale-grey pileus, lageniform caulocystidia, the presence of pileocystidia and cheilocystidia, and ellipsoid basidiospores. Coprinellus aureogranulatus, belonging to section Micacei, is new to China. Phylogenetic analyses based on ITS sequences by the Maximum Likelihood and Bayesian methods showed that C. pseudodisseminatus and C. aureogranulatus are a new and newly recorded species, respectively. Illustrations, photographs, and detailed descriptions of the two species are provided.